Quantitative and Qualitative Responses of Forage Sorghum (Sorghum bicolor L.) to Salinity and Irrigation Frequency - Saberi, Alireza (2011)
In arid and semi arid regions, due to moisture stress from osmotic effects associated with salinity, plant growth tends to be limited. The effects of salinity and irrigation frequency on forage sorghum [Sorghum bicolor (L.) Moench] were evaluated based on experiments conducted in the laboratory and in the field. To determine the germination performance of sorghum under different levels of salinity, seeds of two varieties of sorghum, Speedfeed and KFS4, supplied by the Iran Agriculture Research Organization, were germinated in Petri dishes lined with filter paper, moistened with distilled water (control) or with NaCl concentrations of 5, 10 and 15 dS m-1. Germination percentage, germination rate, germination index and germination coefficient declined with increasing salinity and at 15 dS m-1 the percentage reduction from control was 32.7, 27.7, 28.0 and 6.1%, respectively. Seed germination of KFS4 was higher than Speedfeed.